Optimal. Leaf size=17 \[ 2 x-\frac {1}{3-x+\frac {1}{\log (x)}} \]
________________________________________________________________________________________
Rubi [F] time = 0.66, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {-1+2 x+\left (12 x-4 x^2\right ) \log (x)+\left (17 x-12 x^2+2 x^3\right ) \log ^2(x)}{x+\left (6 x-2 x^2\right ) \log (x)+\left (9 x-6 x^2+x^3\right ) \log ^2(x)} \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {-1+2 x-4 (-3+x) x \log (x)+x \left (17-12 x+2 x^2\right ) \log ^2(x)}{x (1-(-3+x) \log (x))^2} \, dx\\ &=\int \left (\frac {17-12 x+2 x^2}{(-3+x)^2}+\frac {-9+5 x-x^2}{(-3+x)^2 x (-1-3 \log (x)+x \log (x))^2}-\frac {2}{(-3+x)^2 (-1-3 \log (x)+x \log (x))}\right ) \, dx\\ &=-\left (2 \int \frac {1}{(-3+x)^2 (-1-3 \log (x)+x \log (x))} \, dx\right )+\int \frac {17-12 x+2 x^2}{(-3+x)^2} \, dx+\int \frac {-9+5 x-x^2}{(-3+x)^2 x (-1-3 \log (x)+x \log (x))^2} \, dx\\ &=-\left (2 \int \frac {1}{(-3+x)^2 (-1-3 \log (x)+x \log (x))} \, dx\right )+\int \left (2-\frac {1}{(-3+x)^2}\right ) \, dx+\int \left (-\frac {1}{(-3+x)^2 (-1-3 \log (x)+x \log (x))^2}-\frac {1}{x (-1-3 \log (x)+x \log (x))^2}\right ) \, dx\\ &=\frac {1}{-3+x}+2 x-2 \int \frac {1}{(-3+x)^2 (-1-3 \log (x)+x \log (x))} \, dx-\int \frac {1}{(-3+x)^2 (-1-3 \log (x)+x \log (x))^2} \, dx-\int \frac {1}{x (-1-3 \log (x)+x \log (x))^2} \, dx\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.20, size = 27, normalized size = 1.59 \begin {gather*} \frac {1}{-3+x}+2 x+\frac {1}{(-3+x) (-1-3 \log (x)+x \log (x))} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.60, size = 28, normalized size = 1.65 \begin {gather*} \frac {{\left (2 \, x^{2} - 6 \, x + 1\right )} \log \relax (x) - 2 \, x}{{\left (x - 3\right )} \log \relax (x) - 1} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [B] time = 0.23, size = 31, normalized size = 1.82 \begin {gather*} 2 \, x + \frac {1}{x^{2} \log \relax (x) - 6 \, x \log \relax (x) - x + 9 \, \log \relax (x) + 3} + \frac {1}{x - 3} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.05, size = 30, normalized size = 1.76
method | result | size |
norman | \(\frac {-17 \ln \relax (x )-2 x +2 x^{2} \ln \relax (x )-6}{x \ln \relax (x )-3 \ln \relax (x )-1}\) | \(30\) |
risch | \(\frac {2 x^{2}-6 x +1}{x -3}+\frac {1}{\left (x -3\right ) \left (x \ln \relax (x )-3 \ln \relax (x )-1\right )}\) | \(36\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.39, size = 28, normalized size = 1.65 \begin {gather*} \frac {{\left (2 \, x^{2} - 6 \, x + 1\right )} \log \relax (x) - 2 \, x}{{\left (x - 3\right )} \log \relax (x) - 1} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 5.54, size = 21, normalized size = 1.24 \begin {gather*} 2\,x-\frac {\ln \relax (x)}{3\,\ln \relax (x)-x\,\ln \relax (x)+1} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.16, size = 24, normalized size = 1.41 \begin {gather*} 2 x + \frac {1}{- x + \left (x^{2} - 6 x + 9\right ) \log {\relax (x )} + 3} + \frac {1}{x - 3} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________